Individual Differences in Sustained Attention: Effects of Age, Sex, and Time of Day Based on Psychomotor Vigilance Task Performance - Emi Yuda; Yutaka Yoshida (Applied Sciences)
Sustained attention is a critical cognitive function, especially in contexts such as driving safety, where performance deterioration due to fatigue or drowsiness can have serious consequences. Although individual differences in sustained attention have been recognized and are known to decline with age, quantitative analyses considering sex and circadian timing are limited. In this study, we analyzed psychomotor vigilance task (PVT) data from 356 participants to investigate the effects of age, sex, and time of day on attention performance. Participants completed a 5-min PVT, and metrics including the reaction time (RT), minor lapses (MNLs, ≥5 ms), major lapses (MJLs, ≥8 ms), and false starts (FSs) were calculated. A general linear model was applied with sex and testing time (8:00–12:00, 13:00–16:00, 16:00–18:00) as fixed factors and age as a covariate. Stepwise multiple regression was also used to assess how well age, sex, and time of day explain performance. The RT showed significant differences by time and age (p < 0.001), with higher numbers of MNLs during morning sessions. Both sexes demonstrated significantly better performance in the afternoon compared to the morning. These results highlight the importance of controlling for the testing time in PVT-based experiments and underscore the measurable individual differences in sustained attention.